GE_GERICHTE C/18149/2017 vom 24. April 2018 - GE Cour de justice (2018)
PROTECTION DE L'UNION CONJUGALE ; OBLIGATION D'ENTRETIEN ; TRAIN DE VIE ; CONJOINT ; ENFANT DU CONJOINT ; DÉBUT | CC.159.al3; CC.176.al1.let1; CC.278.al2